Upaya Toleransi Umat Bergama terhadap Kaum Minoritas Kristen Katolik di Desa Pamongan, Kota Denpasar, Bali - Nasirudin Al Ahsani (Jurnal Al-Hikmah, 2022)
Indonesia is a multicultural country, namely a country that has a diversity of religions, cultures, ethnicities, races and languages. But on the other hand, religious discrimination is still found in some areas. For the past five years, the Yasmin GKI (Indonesian Catholic Church) congregation has been adrift in legal uncertainty over the sealing and closing of their church building by the Bogor City Government. in the Province of Bali in the field of education, in public schools, if there is a Muslim student who does not have intelligence or excellence, he will be excluded. In the bureaucracy, the opportunity to occupy the position of regent or governor is very difficult for minority groups, especially after regional autonomy. The highest positions that can be occupied by minorities are only lurah and section heads. The aims of this study are: 1) to find out the forms of discrimination that are felt by minorities in Pamongan Village, Desanpasar, Bali; 2) to find out the efforts made to increase tolerance. The method used in this research is descriptive qualitative method. The results of this study are: 1) the forms of discrimination that exist are cultural discrimination such as the distribution of free groceries, sometimes in some areas in Bali it prioritizes the majority religion and discrimination in cyberspace in the form of netizen comments in the Instagram comments column. 2) tolerance efforts are carried out through inter-religious dialogue in the Pamongan Village environment, the ngejot tradition by giving food to people of other religions, and respecting other religious holidays such as Nyepi. Tolerance efforts made by the government by facilitating security in every place of worship when there is a big ceremony